Penyelesaian Kredit Macet dengan Jaminan Hak Tanggungan Pada Bank Syariah Indonesia - Ulil Azmi Zare Tanda; I Nyoman Putu Budiartha; Indah Permatasari (Warmadewa Press, 2022)
The thesis research was motivated by the existence of bad loans that occurred in Indonesian Islamic Banks and also the settlement of mortgage guarantees which did not only occur in conventional banks but also occurred in Islamic banks. The discussion in this thesis is the regulatory mechanism and efforts to resolve the bad loans that occurred at Bank Syariah Indonesia. This research is a normative study to determine the procedure for resolving bad credit disputes with mortgage guarantees at Islamic banks. The discussion in this thesis is to discuss the arrangements and ways of resolving bad credit disputes so that these problems can be resolved in the future. The conclusion that can be drawn from this paper is the arrangement for the settlement of bad loans with mortgage guarantees at Islamic banks, efforts to overcome bad loans that can be done in 2 ways, namely litigation and non-litigation. Efforts to prevent bad loans at Bank Syariah Indonesia can be carried out by applying the precautionary principle and the 5C principle. This principle is a guideline used by banks to give approval to a credit application.